Wuhan. Diari da una città chiusa: memoria storica o tradimento? (Altre Modernità, 2022)
Since January 2020, the Covid-19 began to spread around the world. Wuhan, as the centre of the epidemic in China at that time, endured various difficulties such as blockade and shortage of medical resources. Under such difficulties, some writers tried to create new works. Among them, Fang Fang's Wuhan Diary has received a lot of attention both in China and internationally. It describes the difficulties both physical and psychological under the lockdown, and also criticizes the inaction of some bureaucracies and the dereliction of duty by some officials. After "Wuhan Diary" was translated into different languages and published in various countries overseas, there were many criticisms in China. These criticisms can be summarized into three aspects: First, lack of authenticity; second, the narrative is one-sided and cannot represent the life of Wuhan people; third, publishing overseas is a betrayal of the country. At the same time, there are voices of support. Some netizens believe that Fang Fang has discovered social problems, which is a kind of progress. The reason for the criticism is that the Wuhan described by Fang Fang failed to satisfy the Chinese people's desire for positive energy under the epidemic. In addition, exposing the suffering of Wuhan people to the world seems to be a very “losing face” behaviour, and “face” is the cornerstone of Chinese society. Can Wuhan Diary be both a story of the city and a betrayal of the nation?
Keywords: Wuhan Diary; Fang Fang; historical memory; national betrayal; Covid-19